Cell-Mediated Immunity to Target the Persistent Human Immunodeficiency Virus Reservoir - Riley, James L.; Montaner, Luis J. (The Journal of infectious diseases, 2017)
Effective clearance of virally infected cells requires the sequential activity of innate and adaptive immunity effectors. In human immunodeficiency virus (HIV) infection, naturally induced cell-mediated immune responses rarely eradicate infection. However, optimized immune responses could potentially be leveraged in HIV cure efforts if epitope escape and lack of sustained effector memory responses were to be addressed. Here we review leading HIV cure strategies that harness cell-mediated control against HIV in stably suppressed antiretroviral-treated subjects. We focus on strategies that may maximize target recognition and eradication by the sequential activation of a reconstituted immune system, together with delivery of optimal T-cell responses that can eliminate the reservoir and serve as means to maintain control of HIV spread in the absence of antiretroviral therapy (ART). As evidenced by the evolution of ART, we argue that a combination of immune-based strategies will be a superior path to cell-mediated HIV control and eradication. Available data from several human pilot trials already identify target strategies that may maximize antiviral pressure by joining innate and engineered T cell responses toward testing for sustained HIV remission and/or cure.